Pharmacological characterization of store-operated calcium channels (SOCC) in myometrium of non-pregnant buffaloes (Bubalus bubalis) - SHARMA, ABHISHEK; NAKADE, UDAYRAJ P; CHOUDHURY, SOUMEN; YADAV, RAJKUMAR SINGH; GARG, SATISH KUMAR (The Indian Journal of Animal Sciences, 2018)
Present study unravels the existence and functional involvement of store-operated calcium channels in myometrium of non-pregnant buffaloes. Uteri along with ovaries were collected from nondescript adult cyclic buffaloes immediately after their slaughter from the local abattoir. Under a resting tension of 2 gm, effect of CaCl2 in the absence and presence of different blockers/modulators of calcium regulatory pathways was recorded. CaCl2 produced concentration-dependent contraction and the DRCs of CaCl2 were significantly (P < 0.05) shifted to right in the presence of nifedipine (1 μM) + CPA (10 μM) and nifedipine (1 μM) + CPA (10 μM) + 2-APB (10 μM). After incubation of myometrial strips with nifedipine + CPA in Ca2+ free RLS (-Ca2+), histamine was added to the tissue bath to allow the release of Ca2+ from SR while having already blocked the SERCA by CPA (10 μM) to prevent the Ca2+ reuptake into SR and nifedipine was used to prevent entry of Ca2+ from VDCC when calcium chloride was added and 2-aminoethoxydiphenyl borate (2-APB) (10 μM) was used as a non-specific blocker of store-operated calcium channels (SOCC). In the presence of nifedipine + CPA + 2-APB, calcium chloride produced contractile effect and the maximal contraction observed was only 0.62±0.14 g (n=6) which was significantly (P